Web application - What makes it secure or insecure? - Abdul Aziz, Normaziah; Zainuddin, Nor Harisah (IIUM Press, 2011)

(untitled)
Web applications are among technologies that support the efficiency of our daily activities. Despite the convenience and productivity they can offer, the applications' security loopholes may cause us a hefty amount of unpleasant suffering. Hence, web application developers and users need to understand what causes the applications to be secure and insecure. This chapter discusses some of the characteristics of secure and insecure web applications. Having known these features will make the software development team (designer,developer and tester) incorporates the important preventive measurements. As for customers and users, they can benefit the knowledge by knowing what needs to be in placed to ensure their applications are not vulnerable.